Prepared for what? Brazilian debate on military competence for public security operations - Succi Junior, David P. [UNESP] (Taylor & Francis, 2024)
The military domestic deployment in operations involving the use of force attracted particular attention in the last decades for challenging the traditional conception of the armed forces as instruments of foreign policy. It led to concerns about the adequacy of military training and equipment to act domestically against nonmilitary actors, which can be divided into three arguments: training adequacy, threat adequacy, and pragmatism. The present paper argues that these perspectives are embedded in contrasting normative conceptions about how the state’s violence is to be organized. In this sense, the technical narrative works as a mechanism of legitimation, through which claimants convey a sense of obviousness about the armed forces’ deployment, framing it as the only course of action available. This argument is developed through the analysis of the public debate on three military operations in Brazil: Operation Rio (1994–1995), Operation Arcanjo (2010–2012), and Operation Rio de Janeiro (2017–2018).
Keywords: Armed forces; blurring; Brazil; security